The correlation between multimodal radiomics and pathology about thermal ablation lesion of rabbit lung VX2 tumor - Chen, Jin; Yan, Yuan; Lin, QingFeng; Chen, Jian; Chen, Jie; Lin, ZhengYu (Frontiers in Oncology, 2022)
Objective: Explore the correlation with CT-MRI-pathology about lung tumor ablation lesions by comparing CT, MRI and pathological performance of rabbit lung VX2 tumor after thermal ablation. Methods: Thermal ablation including microwave ablation (MWA) and radiofrequency ablation (RFA) were carried out in 12 experimental rabbits with lung VX2 tumor under CT guidance. CT and MRI performance were observed post-ablation immediately and then executed for pathologic examination. The maximum diameter of tumors on CT before ablation, the central hypointense area on T2WI after ablation, the central hyperintense area on T1WI after ablation and pathological necrosis were measured respectively. Simultaneously, the maximum diameter of ground-glass opacity (GGO) around the lesion on CT after ablation, the surrounding hyperintense area on T2WI after ablation, the surrounding iso-intense area on T1WI after ablation and pathological ablated area were measured respectively, then compared and analyzed the results. Results: Ablation zones showed GGO surrounding the original lesion on CT, with central hypointense and peripheral hyperintense zone on T2WI as well as central hyperintense and peripheral iso-intense on T1WI. There was statistical significance in comparison of the maximum diameter of the tumor before ablation with central hyperintense on T1WI after ablation and pathological necrosis. There was also statistical significance in comparison of the maximum diameter of GGO around the lesion on CT with surrounding hyperintense on T2WI and iso-intense on T1WI after ablation, and pathological ablated zone. There was only one residual tumor abutting the vessel in RFA group. Conclusions: MRI manifestations of thermal ablation of VX2 tumor in rabbit lung have certain characteristics with strong pathological association. CT combined with MRI multimodal radiomics is expected to provide an effective new method for clinical evaluation of the immediate efficacy of thermal ablation of lung tumors.